Representing israel in modern egypt : ideas, intellectuals and foreign policy from nasser to mubarak - Stein, Ewan. ([S.l.] : I. B. Tauris, 2012)
From the heady days of Nasser's Arab nationalism to the cold peace of the Mubarak era, the idea and reality of Israel has occupied a central position in Egyptian politics. Ewan Stein seeks to explain and historicize the state of "no war, no peace" that followed the 1979 Camp David Accords, examining the way in which domestic factors interact with global and regional shifts to shape attitudes to Israel in the Arab world's most populous country. Incorporating the writings of prominent political thinkers, this book looks at how approaches to Israel have been elaborated through broader ideologies - in particular liberal nationalism, Marxism, and Islamism. It argues that representations of Israel have reflected Egyptian conceptions of self. This book provides original and nuanced insights into the relationships between state, society, and foreign policy within the context of Egyptian nationalism and broader regional politics.
Keywords: Egypt; International relations; Israel